Identification of microsatellite loci according to BAC sequencing data and their physical mapping to the bread wheat 5B chromosome - M. A. Nesterov; D. A. Afonnikov; E. M. Sergeeva; L. A. Miroshnichenko; M. K. Bragina; A. O. Bragin; G. V. Vasiliev; E. A. Salina (Вавиловский журнал генетики и селекции)
The shortage of polymorphic markers for the regions of wheat chromosomes that encode commercially valuable traits determined the need for studying wheat microsatellite loci. In this work, SSR markers for individual regions in the short arm of bread wheat chromosome 5B (5BS) were designed based on sequencing data for BAC clones, and the regions of the corresponding chromosome were saturated with these markers. Totally, 130 randomly selected BAC clones from the 5BS library were sequenced on the Ion Torrent platform and assembled in contigs using MIRA software. The assembly characteristics (N50 = 4 136 bp) are comparable to the recently obtained data for wheat and relative species and acceptable for identification of microsatellite loci. An algorithm utilizing the properties of complexity decompositions in  he sliding-window mode was used to detect DNA sequences with a repeat unit of 2–4 bp. Analysis of 17 770 contigs with the total length of 25 879 921 bp allowed for designing 113, 79, and 67 microsatellite (SSR) loci with a repeat unit of 2, 3, and 4 bp, respectively. The SSR markers with a motif of 3 bp were tested using nullitetrasomic lines of Chinese Spring wheat homoeologous group 5. Thus, 21 markers specific for chromosome 5B were detected. Eight of these markers were mapped to the distal region of this chromosome (bin 5BS6) using a set of Chinese Spring deletion lines for 5BS. Eight and four markers were mapped to the interstitial region (bins 5BS5 and 5BS4, respectively). One marker was mapped to a pericentromeric bin. A comparative analysis of the distribution of trinucleotide microsatellites over wheat chromosome 5B and in different cereal species suggests that the (AAG)n repeat has proliferated and has been maintained during the evolution of cereals.